Ghana : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This 2013 Article IV Consultation highlights that economic growth in Ghana continued at a robust pace of 8 percent in 2012 amid rising fiscal and external imbalances. Fiscal pressures came to the fore in a mounting public sector wage bill and costly energy subsidies that pushed the deficit close to 12 percent of GDP. The growth momentum continues into 2013, with increased oil production projected to keep overall GDP growth close to 8 percent. Non-oil growth is likely to decelerate, however, as a result of energy disruptions and high real interest rates.